International Liver Transplantation Society Consensus Statement on Immunosuppression in Liver Transplant Recipients. Issue 5 (May 2018) - Charlton, Michael; Levitsky, Josh; Aqel, Bashar; O'Grady, John; Hemibach, Julie; Rinella, Mary; Fung, John; Ghabril, Marwan; Thomason, Ray; Burra, Patrizia; Little, Ester Coelho; Berenguer, Marina; et al.
Abstract : Abstract: Effective immunosupression management is central to achieving optimal outcomes in liver transplant recipients. Current immunosuppression regimens and agents are highly effective in minimizing graft loss due to acute and chronic rejection but can also produce a substantial array of toxicities. The utilization of immunosuppression varies widely, contributing to the wide disparities in posttransplant outcomes reported between transplant centers. The International Liver Transplantation Society (ILTS) convened a consensus conference, comprised of a global panel of expert hepatologists, transplant surgeons, nephrologists, and pharmacologists to review the literature and experience pertaining to immunosuppression management to develop guidelines on key aspects of immunosuppression. The consensus findings and recommendations of the ILTS Consensus guidelines on immunosuppression in liver transplant recipients are presented in this article. Abstract : The ILTS consensus document on immunosuppression in liver transplant recipients covers both the scope of therapeutic agents for induction and rejection therapy as well as an overview of complications and clinical management.